(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2016)
The effect of residual stresses and the lubricant type in grinding on the characteristics of magnetic Barkhausen noise (MBN) profiles were examined in low alloy steel of the type used for wear-resistant engineering components. A shotpeened and ground in different conditions specimens were tested. MBN measurements showed that the intensity of the signal increases with abusive grinding due to residual tensile stresses and decreases with shot peening due to residual compressive stresses. An increase was seen in wet grinding specimens as compared with the heat-treated specimen. The increase in MBN after grinding was due to local heating with transition from the initial stage of strong martensitic structure, with residual stress of compression, to the following stage of lower hardening with tendency to residual stress of tensile character. In addition, Barkhausen signals from surfaces ground under controlled conditions were found to be dependent on the lubricant type. The decrease in MBN after shotpeening was due to the accumulation of residual compressive stresses introduced to the martensitic structure. The observations are discussed in the light of established models of Barkhausen noise.